Regulation of human embryonic globin genes zeta 2 and epsilon in stably transformed mouse erythroleukemia cells. - Vyas, P; Sharpe, J; Watt, P; Higgs, D; Wood, W (1992)
Previous work has suggested that the promoter regions of the human embryonic zeta 2 and epsilon globin genes contain negative regulatory regions that could play a role in the repression of these genes in postembryonic erythroblasts. We have examined this possibility by studying the expression of these genes in mouse erythroleukemia cells, an adult erythroid cell line that might be expected to contain repressor molecules that would bind to the putative negative regulatory regions. When attached to appropriate upstream regulatory elements (alpha HS-40 and beta HS1,2) both the zeta and epsilon genes were expressed in these cells at a low level, but no increase in expression was observed when similar constructs lacking the proposed negative regulatory sequences were introduced into these cells. These results cast doubt on the possibility that these sequences play a major role in the developmental repression of the embryonic globin genes, unless they function only in a normal chromosomal organization.